Multiple health risk behaviors, including high consumption of ultra-processed foods and their implications for mental health during the COVID-19 pandemic - Hillary Nascimento Coletro; Raquel de Deus Mendonça; Adriana Lúcia Meireles; George Luiz Lins Machado-Coelho; Mariana Carvalho de Menezes (Frontiers in Nutrition, 2022)
Background and aimThe growing increase in diet- and behavior-related illnesses has drawn the attention of many epidemiologists who attribute such changes to the epidemiological and nutritional transition. Thus, this study aims to evaluate the association between the combined occurrence of health risk behaviors, such as sedentary lifestyles, high weekly consumption of ultra-processed foods (UPFs), and non-daily consumption of fruits and vegetables, and symptoms of anxiety or depression in adults.MethodsThis is a cross-sectional study based on an epidemiological survey in two Brazilian cities. The outcome, anxiety, and depression symptoms were assessed using the Generalized Anxiety Disorder 7-item (GAD-7) and the Patient Health Questionnaire-9 (PHQ-9). Food consumption was assessed using a qualitative food frequency questionnaire (FFQ) with reference to consumption in the last 3 months and categorized into the consumption of fruits and vegetables and the consumption of UPFs according to the NOVA classification. Sedentary behavior was assessed by considering the amount of sitting or reclining time per day reported by participants and categorized as less than 9 h of sitting or reclining and 9 h or more. For the analysis, adjusted Poisson regression (PR) was used to estimate the prevalence ratio and the 95% confidence interval (CI).ResultsThose with the health risk behaviors, non-daily consumption of fruits and vegetables, and high consumption of UPFs had a 2.6 higher prevalence ratio for symptoms of mental disorder (PR: 2.6 and 95%CI: 1.1–6.5), as well as those with all three health risk behaviors, had a 2.8 higher prevalence ratio for symptoms of mental disorder (PR: 2.8 and 95%CI: 1.3–6.1).ConclusionThis study revealed that the existence of a combination of two and three health risk behaviors led to a higher prevalence of symptoms of anxiety or depression.